Comparative outcomes between surgical treatment and orthosis splint for mallet finger: a systematic review and meta-analysis. Issue 1 (28th February 2023) - Peng, Chi; Huang, Ren-Wen; Chen, Shih-Heng; Hsu, Chung-Chen; Lin, Cheng-Hung; Lin, Yu-Te; Lee, Che-Hsiung
Abstract: Mallet finger is a commonly encountered condition in daily practice. However, there is currently no consensus on whether surgical intervention or conservative treatment with orthosis splint is superior. In this systematic review and meta-analysis, we compare the treatment outcomes between surgery and orthosis for bony and tendinous mallet finger. We searched PubMed, Embase, and the Cochrane Library according to the PRISMA guidelines from inception to January 15, 2021. The primary outcome was distal interphalangeal (DIP) joint extension lag angle, and secondary outcomes were DIP joint flexion and range of motion (ROM) angle. A total of 297 studies were initially identified, of which 13 (ten retrospective non-randomized controlled studies (non-RCTs) and three RCTs) were included in the final analysis. The results of this systematic review and meta-analysis showed that there was no high level of evidence supporting the superiority of surgery over orthosis in the treatment of mallet finger. Based on the available evidence, surgical intervention and conservative treatment with splint may offer similar clinical outcomes in both bony and tendinous mallet finger.